PENINGKATAN DAYA INGAT SISWA TERHADAP PEMBELAJARAN MATEMATIKA DENGAN PENGGUNAAN TEKNIK MNEMONIC PADA KELAS XI MAS AL-BARAKAH - Anggriyani, Ike; Hrp, Nurlina Ariani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study used a pre-experimental research method to determine the increase in memory of class XI MAS Al-Barakah students on learning mathematics by applying mnemonic techniques. The subjects in this study were 20 students of class XI MAS Al-Barakah. The instrument used in this study was a description test of 7 questions which had been adjusted to the memory indicators. then this essay test is given in accordance with the research design used in this study is the One-Group Post-Re-Test. However, before the posttest and re-test research, first a pretest test was given to determine students' memory. The results of each test were given with a low level of student memory pretest, namely 35%, and posttest giving students a moderate level of memory, namely 55%. So it can be concluded that the more often given the test, the better the memory of the students. an increase in student memory. Thus, the results of this study indicate an increase in the memory of class XI MAS Al-Barakah students towards learning mathematics by using mnemonic techniques.